Bibliometric Analysis of the Application of Internet of Things (IoT) in Financial Services - Judijanto, Loso; Fildansyah, Rully; Sudarmanto, Eko; Harsono, Iwan; Afandy, Chairil (Westscience Press, 2024)
This study presents a comprehensive bibliometric analysis of the application of Internet of Things (IoT) in financial services. The analysis encompasses a systematic review and analysis of existing literature, identifying key research themes, trends, and patterns in the field. Through the utilization of bibliometric indicators such as co-citation analysis, keyword co-occurrence analysis, and citation network analysis, the intellectual structure of the domain is mapped, uncovering emerging research topics and areas of focus. The study also provides insights and recommendations for future research directions and practical implications. The findings contribute to advancing our understanding of IoT's role in reshaping financial services and offer guidance for researchers, policymakers, and industry stakeholders.